Clinical supervision of teachers: The striving for relevance - Myers, Samuel S. (Institute of Social and Economic Research, UWI, 1996)
This chapter discusses the problems of teacher supervision and attempts to provide a definition of clinical supervision
Keywords: Teacher supervision